Faktor- Faktor Yang Mempengaruhi Diversifikasi Portofolio Pada Investor Ritel - Ardiansyah, M.; Leon, Farah Margaretha (Manajemen Bisnis Kompetensi, 2018)
This study examined the effect of Financial Literacy and the Retail Investor Portfolio. Data obtained directly by distributing questionnaires to 190 respondents to the independent investor. The research design used in this study is hypothesis testing. The analytical method used in this research is multiple regression. The results of this study were (1) Age does not affect the Portfolio diversification. (2) Gender positive effect on portfolio diversification. (3) Income does not affect the Diversified Portfolio (4) Financial Literacy does not affect the Portfolio diversification. (6) does not affect the size of the Portfolio Diversification Portfolio (6) Familiarity negative effect on portfolio diversification. (7) Availability positive effect on Diversified Portfolio (8) Too Believe positive effect on portfolio diversification. So with that can be input and learning to the Indonesia Stock Exchange to provide assistance and services to companies that want to do the listing on the Indonesia Stock Exchange. Keywords: portfolio diversification, demographic factors, availability, familiarity, financial literacy, overconfidence, portfolio size